Patriotism, patriarchy and purity: Natal and the politics of Zulu ethnic consciousness - Marks, Shula (My University, 1986)
On 5 August 1985, the violence which had already led to a State of Emergency in much of South Africa exploded in Natal, leaving more than seventy people dead and thousands injured and homeless in the course of a week and raising the spectre in some areas of a repetition of the anti-Indian riots of 1949. In 1985 at least half the dead were shot by the police, and it would be foolish to see the disturbance in simple racial terms. Political differences between the newly formed United Democratic Front and the Zulu cultural movement, Inkatha, and sheer economic deprivation which led to the looting of African as well as Indian traders, warn against any simple equation of the violence with racially motivated anti-Indian sentiment per se.
African Studies Seminar series. Paper presented 4 August 1986
Keywords: Zulu (African people). South Africa. KwaZulu-Natal. Ethnic identity; KwaZulu-Natal (South Africa). Politics and government; Ethnicity. South Africa. KwaZulu-Natal; Zulu (African people). Ethnic identity